2009
DOI: 10.1177/1460458208099865
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone text messaging to promote healthy behaviors and weight loss maintenance: a feasibility study

Abstract: There is a need to investigate newer strategies pertaining to the maintenance of healthy behaviors and weight. We investigated the feasibility of mobile phone text messaging to enable ongoing communication with African-American women participating in a weight management program. Ninety-five African-American women participated in this pilot study and received regularly scheduled text messages. Forty-two of these women chose to create 165 personal text messages that included tips on healthy eating and physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
167
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(178 citation statements)
references
References 21 publications
9
167
1
1
Order By: Relevance
“…Deleting messages or full conversations is also important because sometimes the users want to clean the text on the screen or just to save some memory space on their device [40,41].…”
Section: Step 3: Identify the Primary Operating Functions And Excludementioning
confidence: 99%
“…Deleting messages or full conversations is also important because sometimes the users want to clean the text on the screen or just to save some memory space on their device [40,41].…”
Section: Step 3: Identify the Primary Operating Functions And Excludementioning
confidence: 99%
“…Continued research will be needed to determine optimal modalities, frequencies, and durations of such follow-up methods, especially because many participants might be averse to engaging in lengthy or intensive treatment sessions over the long term. Although some research indicated the possible helpfulness of phone-and/or Internet-based follow-up messages [51,52], the associated research is in its early stages and the efficacy of those modalities remains unclear [6]. It is also possible that follow-up protocols should be tailored by individual factors (e.g., amount of weight lost and regained, psychological make-up).…”
Section: Discussionmentioning
confidence: 99%
“…However, our satisfaction data showed that the text messages were well-received, similar to the study conducted by McCoy et al [26] and another weight loss study in African American women. [27] Even more importantly, the majority of participants responded to the text messages even though they were not required to do so, and that greater text message response was associated with greater percent body fat loss. Comparison with prior work: The LEAN study is one of numerous church-based translational weight loss programs targeting African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…[22] This realization has led to the development of mHealth pilot and feasibility studies targeting heart disease management, [23] diabetes, [24] physical activity, [25,26] and weight loss maintenance. [27] Although these studies demonstrate the acceptability, feasibility, and potential effectiveness of mHealth interventions designed for African American adults, few have utilized randomized controlled designs and few were specifically designed to promote weight loss. Therefore, the purpose of the Lifestyle Changes Through Exercise and Nutrition (LEAN) study was to test the feasibility and effectiveness (compared to a control group) of utilizing text messages to promote weight loss in African American adults enrolled in a church-based weight loss program.…”
Section: Introductionmentioning
confidence: 99%